Development Strategy for Waisia ​​Waterfall Tourism Object in Rumahkay Village, West Seram Regency - Pattipelohy, Wendy; Tetelepta, Edward Gland; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2024)
As one of the tourist destinations, Maluku Province certainly also has several exciting waterfall tours, including Waisia ​​Waterfall. Waisia ​​Waterfall is one of the natural tourist attractions in Rumahkay Village. Waisia ​​Waterfall has excellent water and clean air. The problem in this study is how to develop the Waisia ​​waterfall tourist attraction in Rumahkay Village, West Seram Regency. This study aims to determine the strategy for creating the Waisia ​​Waterfall Tourist Attraction. This type of research is descriptive research, Which is a method widely used in research that aims to explain an event. "Descriptive research is a study that seeks to provide or describe a condition or phenomenon that is currently occurring using scientific procedures to answer problems in an actual manner. The Waisia ​​Waterfall Tourist Attraction Area in West Seram Regency can be said to have quite a lot of potential for developing tourism, based on the results of the SWOT analysis. The IFAS (strengths and weaknesses) and EFAS (opportunities and threats) scores are post value. So, the Waisia ​​Waterfall Tourism Object Development Strategy in West Seram Regency shows quadrant 1: the strength and opportunity (SO) Strategy. Improving the quality of facilities and infrastructure to support the development of the Waisia ​​Waterfall Tourism Object, Maximizing the management of tourism potential, and Community Participation in preserving Nature.